The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2147/ijn.s62837
|View full text |Cite
|
Sign up to set email alerts
|

Bio-functionalized dense-silica nanoparticles for MR/NIRF imaging of CD146 in gastric cancer

Abstract: Purpose Nano dense-silica ( d SiO 2 ) has many advantages such as adjustable core–shell structure, multiple drug delivery, and controllable release behavior. Improving the gastric tumor-specific targeting efficiency based on the development of various strategies is crucial for anti-cancer drug delivery systems. Methods Superparamagnetic iron oxide nanoparticles (SPION) were coated with d Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 14 publications
0
16
0
2
Order By: Relevance
“…MCAM is also involved in several cellular processes including cell invasion, migration, angiogenesis, epithelial mesenchymal transition, immune response, and signal transduction (10). Additionally, MCAM has low expression levels in normal tissue, primarily restricted at intracellular junctions of endothelial cells (10,11). Previous studies have shown differential expression of MCAM in primary tumors correlated with metastasis and poor prognosis in several cancers, showing its significant potential in cancer therapy (1214).…”
Section: Introductionmentioning
confidence: 99%
“…MCAM is also involved in several cellular processes including cell invasion, migration, angiogenesis, epithelial mesenchymal transition, immune response, and signal transduction (10). Additionally, MCAM has low expression levels in normal tissue, primarily restricted at intracellular junctions of endothelial cells (10,11). Previous studies have shown differential expression of MCAM in primary tumors correlated with metastasis and poor prognosis in several cancers, showing its significant potential in cancer therapy (1214).…”
Section: Introductionmentioning
confidence: 99%
“…CD146 expression is primarily constrained to the intracellular junctions of endothelial cells and is actively involved in several cellular processes including cell-matrix adhesion, cell migration, signal transduction, stem cell differentiation, immune response, and angiogenesis [12]. Additionally, CD146 has low background levels in normal tissue as well as differential expression in metastases and advanced primary tumors, showing its significant potential in cancer therapy [12, 13]. We have previously shown that persistent and specific targeting of CD146 in vivo may be accomplished with the monoclonal antibody known as YY146 [14].…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, the most immunoreactive antibody clones were determined by ELISA and further evaluated with YY146 showing optimal properties for continued investigation [14]. To date, the use of YY146 has been limited to brain and gastric cancer with both diseases showing high levels of CD146 expression and high uptake of YY146 [13]. PET imaging of YY146 allowed for visualization of small tumor nodules with high specificity in glioblastoma multiforme [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, the silica shell can ensure an enough distance between the Fe 3 O 4 core and fluorescent tracers to prevent the fluorescence quenching effect. For example, the fluorescent signals of fluorescent dyes modified on the surface of silica shell or encapsulated with silica could track the process of targeted drug delivery by fluorescence microscopy . In addition, silica exhibits a negative surface charge under physiological condition, and the silanol groups make the particle surfaces lyophilic, thus, enhancing the stability of their suspensions, even when the pH or electrolyte concentrations are changed …”
Section: Anticancer Drug Delivery Systems Based On Inorganic Nanocarrmentioning
confidence: 99%